Drivers and pathways for Ethiopia's 2050 decarbonization: An integrated LMDI LEAP modeling framework - Belay Sitotaw Goshu (Budapest International Research in Exact Sciences (BirEx) Journal, 2026)
Ethiopia has sustained rapid economic growth (6-10 percent annually) but remains heavily dependent on traditional biomass (88 percent of final energy), with electrification at only 55 percent as of 2022. Ambitious climate targets under NDC 3.0 (70.3 percent reduction below BAU by 2035) and the Long Term Low Emissions Development Strategy (net zero by 2050) demand rigorous decarbonization planning. This study develops an integrated LMDI LEAP framework to assess Ethiopia's decarbonization pathways to 2050, bridging historical driver decomposition with dynamic scenario simulation. Methods: Logarithmic Mean Divisia Index (LMDI) decomposition quantifies drivers of energy related CO2 emissions (2005-2020). The Long Range Energy Alternatives Planning System (LEAP) models four scenarios (BAU, Current Policies, Announced Policies Scenario - APS, and Net Zero Emissions - NZE) from 2022 to 2050. LMDI reveals that economic activity (+58 percent) and population (+38 percent) drove emission increases, while energy intensity improvements (-45 percent) partially offset growth, indicating a weak decoupling status (elasticity 0.54). Under BAU, emissions reach 214 MtCO2e by 2060. APS reduces emissions to 65 MtCO2e in 2035 (42 percent below BAU), approaching NDC 3.0 unconditional targets. NZE achieves energy sector emissions of 2.9 MtCO2e by 2050 (more than 90 percent reduction) through aggressive efficiency measures. Improved cookstoves reduce household demand by 55-57 percent, combined with full renewable electrification and end use switching. Ethiopia can meet NDC 3.0 targets with moderate policy effort, but achieving net zero requires transformative interventions, particularly in residential cooking and transport, backed by approximately US$157 billion in climate finance. Key priorities include energy intensity improvements, expansion of solar, wind, and geothermal energy, electrification of end uses, and mobilization of international support.